Successive double cropping of potato minitubers under insect proof net house for increased seed productivity - KAUR, R P; DEVI, SUGANI; SINGH, SUKHWINDER; MINHAS, J S; SINGH, A K; RANA, R K; RAWAL, SANJAY; SINGH, R K (The Indian Journal of Agricultural Sciences, 2021)
Non-availability of disease-free quality seed material is the most important factor affecting low productivity of potato in India. Successive cropping of disease free minitubers under net house conditions, in the north western plains of India, can be an important intervention for utilizing this expensive vector free space and prevailing potato growing climate of the region in the most sustainable way. A field study was undertaken during 2016-18 to evaluate this hypothesis for its productivity and economics over single crop conventionally taken in the region. Minitubers of six potato varieties were grown in single and successive cropping patters under net house in the region. The summed yield attributes of their early (DCE) and late planted (DCL) successive crops were compared to single cropping (SC) on per meter square basis. Corresponding observations on morphological traits and yield attributes were quite encouraging. Minituber yield of under size, seed size and combined was 1.99, 1.88 and 1.98 times higher in double crop as compared to conventional single crop. As a result, cost of production declined (2.52 times) and net profit increased (3.15 times) in double crop. Cost of production per tuber was reduced in this technique from ₹ 2.01-1.28 per minituber. Higher profits and productivity under successive planting are achievable and this innovative technology can be easily adopted by the stakeholders for improving multiplication of early generation planting material, which would translate into availability of increased seed material after stipulated multiplications.